The Franks in the Islamic Intellectual Heritage - Ahmad Al-Zubaidi; M.D. Walid Jassim Al-Zubaidi (“ARAB TILI GLOBALLASHUV DAVRIDA: INNOVATSION YONDASHUVLAR VA O‘QITISH METODIKASI” MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2025)
The history of relations between the Franks and the Islamic state is a long history, extending for many centuries, from the beginning of the Islamic message, to the establishment of the Abbasid state in its eras, then the Ayyubid state and the Mamluks, and it was between ebbs and flows, periods of wars, and a period of peace, which affected the regional and international environment and the trade and transportation routes. The Islamic and Frankish nations were influenced by the culture of each nation, and Muslim historians expressed in their works their point of view regarding this relationship. The different names and descriptions of the Franks were (the Franks, the Franks, the Franks, and the Franks), to denote the peoples of Europe, as they described them (the invaders, Enemies, infidels, polytheists, tyrants...) . The religious roots became the main driver behind the theme of this relationship, and the Franks dressed it in the guise of holiness, imbuing it with legitimacy, holy war, and the only means of forgiveness).. The research revealed the economic relations, the development in the agricultural sector and the system of feudalism in the Islamic states and kingdoms that began to disintegrate and fragment, and the social aspect and the moral decomposition that afflicted Islamic societies, prostitution, sexual deviance, and the spread of poverty and banditry. On the cultural and religious side, as a result of the state of disintegration and weakness, a state of isolation and isolation arose, the spread of the phenomenon of Sufism and drusha, the spread of hospices and zawiyas, and the emergence of Sufi sects and various movements, produced by societal reality and the shadows of political reality affected.